1984
DOI: 10.3758/bf03206333
|View full text |Cite
|
Sign up to set email alerts
|

The effects of familiar size on judgments of size and distance: An interaction of viewing attitude with spatial cues

Abstract: Two hypotheses about the effects of familiar size on judgments of size and distance, the cueconflict hypothesis and the viewing-attitude hypothesis, were examined. In Experiment 1, observers estimated the size and distance of familiar targets with apparent or assumptive instructions under three different spatial cue conditions. In Experiment 2, observers performed tasks similar to those of Experiment 1 with no specific instructions. The main results were: (1) Assumptive instructions facilitate the effects of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The latter results are consistent with those ofDa Silva and Dos Santos (1984), who found that the type of instructions, using the magnitude estimation procedure, did not affect the distance responses obtained in a large open field. However, in addition to the effects of instructions on distance responses that Higashiyama (1984) found, Rogers and Gogel (1975) also found some effects under laboratory, full-cue conditions. It is not clear why distance responses were not sensitive to instructions in the present study.…”
Section: Responses To the Playing Cardmentioning
confidence: 84%
See 1 more Smart Citation
“…The latter results are consistent with those ofDa Silva and Dos Santos (1984), who found that the type of instructions, using the magnitude estimation procedure, did not affect the distance responses obtained in a large open field. However, in addition to the effects of instructions on distance responses that Higashiyama (1984) found, Rogers and Gogel (1975) also found some effects under laboratory, full-cue conditions. It is not clear why distance responses were not sensitive to instructions in the present study.…”
Section: Responses To the Playing Cardmentioning
confidence: 84%
“…A recent article by Higashiyama (1984) examines the effect of familiar size upon verbal reports of size and distance as a function of viewing attitude and the level of opposing cues. Three images of the same physical width but differing in familiar size were presented at a constant physical distance to produce simulated distances of 43, 99, and 182 cm.…”
Section: Responses To the Playing Cardmentioning
confidence: 99%
“…In contrast, in only a few studies (Carlson & Tassone, 1971;Fillenbaum, Schiffman, & Butcher, 1965;Higashiyama, 1984;Predebon, 1979aPredebon, , 1979bPredebon, , 1987 has the effect of familiar size on judgments of distance under naturalistic, unrestricted viewing conditions been investigated. In general, the results of these studies indicate that familiar size can be an effective cue to distance, although its effectiveness appears to be contingent on viewing attitude (Higashiyama, 1984) and on the method of measuring perceived distance (Predebon, 1987).…”
mentioning
confidence: 99%
“…Thus, it is unclear whether familiar size determines perceived distance or only allows subjects to make conscious estimates of distance. This criticism, which can apply to all familiar-size studies in which adult subjects make distance judgments, is particularly important in light of a number of studies showing that adult subjects' distance judgments are influenced by such variables as instructions, viewing attitude, and suggested, rather than familiar, size of target objects (Baird, 1963;Coltheart, 1969Coltheart, , 1970Gogel, 1981;Hastorf, 1950;Higashiyama, 1984;Park & Michaelson, 1974). The findings of these studies are consistent with the view that adults' distance judgments in familiar-size experiments may be influenced by factors other than the perceived distances of the stimulus objects.…”
mentioning
confidence: 99%